Genetic diversity of Macaca fascicularis (Cercopithecidae) from Penang, Malaysia as inferred from mitochondrial control region segment - Rovie-Ryan, J. J.; Abdullah, M. T.; Sitam, F. T.; Tan, S. G.; Zainuddin, Z. Z.; Basir, M. M.; Abidin, Z. Z.; Keliang, C.; Denel, A.; Joeneh, E.; Ali, F. M. (Department of Biology, University of Andalas in collaboration with Copenhagen Zoo, 2014)
The genetic diversity of the long-tailed macaques (Macaca fascicularis) from Penang, Malaysia, including Jerejak Island and the mainland area of the state of Penang, Seberang Perai were examined using 1,042 bp control region (CR) segment of the mitochondrial DNA (mtDNA). Twenty haplotypes were described with a single haplotype sharing between the mainland and the island which suggests that it is a remnant of the genetic makeup from the mainland. Compared to previous studies based on the CR, all the Penang haplotypes are newly described with none shared with the other regional populations of M. fascicularis. A single deletion mutation unique to the Penang samples (Groups I and II) could be a good indicator for the conservation of the genetic uniqueness and possibly should be managed as a management unit (MU). A summarised phylogenetic tree (NJ, MP, ML and Bayesian) supports the monophyletic clustering of the M. fascicularis as described in previous studies. The topology separates the Penang haplotypes into three major groups, which generally corresponds to their geographical distribution. We also noted that the Penang haplotypes are of the continental lineage which separated from the insular lineage at around 1.04 mya. Finally, we showed that the CR of the mtDNA is powerful and suitable for the quantification of intraspecific diversity in M. fascicularis.